Erweiterung der Pfahlmuschel- und Austernaufzuchtanlage in der Flensburger Förde - Meixner, R. (1973)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010